Antiviral activity and mechanism of action of edible bird’s nest against influenza A virus strain A/Puerto Rico/8/1934 (H1N1) - Haghani, Amin (2015)
Influenza infection is still a high-risk disease affecting human and different animal species by causative agent influenza A virus (IAV). Currently there is neither effective vaccine nor efficient drug to control this infection. Edible Bird’s Nest (EBN) as a popular traditional Chinese medicine (TCM) is believed to have health enhancing effects like anti-tumor and immunomodulatory activities. These natural extracts also have shown antiviral properties against influenza viruses; however, the molecular mechanism of action of these compounds still is not well characterized. Hence, the first aim of this study was to highlight the inhibitory effects of EBNs against influenza A virus (IAV) infection. Accordingly, house EBNs were collected from Teluk Intan and cave nests from Gua Madai in Malaysia and the extractions were prepared based on the established methods with two different enzymatic treatments. The median cytotoxic concentration (CC50) of the EBN extracts were determined on Madin-Darby canine kidney (MDCK) cell line using microculture tetrazolium (MTT) assay and later on the best exposure way and median inhibitory concentration (IC50) of the EBNs were shown against IAV strain A/Puerto Rico/8/1934 (H1N1). The results showed that post inoculation of the EBNs had the highest antiviral effect against IAV. The CC50 of these compounds ranged from 27.5-32 mg/ml with IC50 of 2.5-4.9 mg/ml against IAV and EBNs from Gua Madai had higher selectivity index compared to Teluk Intan. The second aim of this study was to understand the mechanism of action of these natural compounds against different molecular processes of IAV life cycle. These processes included effect of EBN on four viral proteins, virus host immune interactions through cytokines, early endosomes formation and their trafficking, and lastly autophagy process during IAV infection. Consequently, four viral genes and six cytokines were selected to be analyzed by RT-qPCR and ELISA to elucidate the effect of EBNs on the virus and immune system. Later, Western blotting on three GTPases proteins, and immunofluorescent labeling of actin cytoskleton and lysosomes were done to investigate the effects of EBNs on endocytosis, actin cytoskeleton and macroautophagy processes during influenza virus life cycle. Regarding the effect of EBNs on viral genes and cytokines, the results showed that depends on the EBN composition, EBNs could significantly decrease the extracellular NA and NS1 copy number (p<0.05) of the virus along with high immunomodulatory effects against IAV. EBNs showed antiinflammatory effects through decrease of CCL2 and IL-6, and increase of IL-27. In addition, these compounds might affect the virus by increase of TNF-α and activation of NF-κB. Immunofluorescent staining and Western blot results revealed the effects of EBNs on endocytosis, actin filament polymerization and macroautophagy pathways against IAV. EBNs could affect the trafficking of early endosomes by significant (p<0.05) decrease in GTPase proteins like RAB5 and RhoA, also ameliorating the actin filaments distress. These natural mixtures could efficiently inhibit the autophagy process involved in IAV life cycle by decrease (p<0.05) in LC3-II protein and augmentation of lysosome activity. In conclusion, EBNs can inhibit influenza infection by affecting critical steps of the virus life cycle. EBNs from different locations would show different mechanisms against IAV. Hence, after screening for the composition, these natural remedies have the potential to be used as an alternative antiviral agent against future influenza disasters. Further in vitro and in vivo studies are required to detect the bioactive agents and investigate the clinical applications of this natural medicine against influenza.